The Innovation Of Pizza Basic Sauce Using Asam Pedas Paste From Riau Islands - Adiguna Tumpuan (Universitas Negeri Padang, 2021)
Culinary tourism is one of the most important industries in the world of tourism. Lagoi, which is one of the best tourism destinations in Indonesia, is certainly inseparable from the role of culinary tourism, which will be a means of meeting the basic needs of domestic and foreign tourists. One menu that is very popular in the culinary business is pizza. When making pizza, you usually use a tomato-based sauce, commonly called marinara sauce, as the base sauce. The Riau Archipelago, which is famous for its original culinary delights, also has several spices that are unique to the culinary delights of the Riau Archipelago. One of the most popular seasonings in the culinary delights of the Riau Archipelago is spicy tamarind seasoning. This seasoning is the main seasoning for several marine products in the Riau Archipelago, such as fish, cuttlefish, bark, and others. In this study, the authors will examine the innovation of developing the benefits of a spicy, sour-based seasoning typical of the Riau Islands with Italian pizza preparations through organoleptic tests or sensory analysis to determine the panelists' preference level by combining the spicy-tamarind-based seasoning with original marinara sauce. The purpose of this study was to determine the level of preference of the panelists for the aspects of taste, aroma, color, and texture in the results of an innovative pizza product that uses a combination of spicy and sour basic seasonings and marinara sauce. The results showed that the combination of 50% sour and spicy seasoning and 50% marinara seasoning got the best value in terms of color, taste, texture, aroma, and overall